Core-shell type solid waste-based functional aggregate as well as preparation method and application thereof

By adopting the process of core-shell solid waste-based functional pellets, using materials such as river silt and steel slag, combined with specific chemical components, the problems of high energy consumption and high pollution during the treatment of river silt and steel slag in the existing technology are solved, and the problem of high energy consumption and high pollution during the treatment of river silt and steel slag in the existing technology is achieved. It provides efficient preparation of functional pellets and excellent water treatment performance.

CN119430846AInactive Publication Date: 2025-02-14JIANGSU JICUI FUNCTIONAL MATERIALS RES INST CO LTD

Patent Information

Application Number
CN202510016091.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing technology has problems such as high energy consumption, high pollution, low solid waste mixing, severe odor, low porosity, low strength, insufficient freezing resistance when dealing with river silt and steel slag, and it is difficult to achieve effective comprehensive management and application. .

Method used

Core-shell solid waste-based functional pellets are used, and by using river sludge, steel slag and other materials as core materials and shell materials, combined with hydrogen peroxide, rice husk ash, sodium hydroxide, desulfurization gypsum and other components, through extrusion molding and water By thermal reaction and other processes, functional pellets with good mechanical properties and water treatment functions were prepared.

Benefits of technology

It has achieved comprehensive management of river silt and steel slag, improved the mechanical properties and water treatment effect of functional pellets, and has good structural strength and porosity, which is suitable for water treatment field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses core-shell type solid waste-based functional granules as well as a preparation method and application thereof. The core-shell type solid waste-based functional granules comprise a core material and a shell material coating the surface of the core material, wherein the core material comprises 20-90 parts of river sludge, 1-15 parts of hydrogen peroxide, 10-50 parts of rice hull ash, 1-12 parts of sodium hydroxide and 5-40 parts of desulfurized gypsum; the shell material comprises 10-100 parts of steel slag, 5-40 parts of mineral slag, 5-30 parts of desulfurized gypsum and 2-13 parts of polyvinyl alcohol. According to the invention, comprehensive treatment and application of the river sludge and the steel slag are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid waste treatment, and in particular to a core-shell solid waste-based functional granular material and a preparation method and application thereof. Background Art

[0002] In the process of river channel and related small watershed management, a large amount of river silt will be generated. If these river silts are not effectively treated, they will cause serious environmental problems. At present, the commonly used method is to convert river silt into building materials by sintering, but this method has high energy consumption and high pollution, which seriously affects the back-end implementation scenario. The use of a non-burning method to prepare river silt into ceramsite will have many problems such as low solid waste content, severe odor, low porosity, low strength, and insufficient frost resistance.

[0003] In addition, steel slag, as one of the important components of cement, also faces the problem of environmental pollution after the release of the new national standard for cement. At the same time, the free calcium oxide in steel slag will also cause huge problems in its application process. Based on this, it is necessary to study an effective treatment method for the above solid waste materials to adapt to more application scenarios. Contents of invention

[0004] In order to overcome the above-mentioned shortcomings, the purpose of the present invention is to provide a core-shell solid waste-based functional granular material and a preparation method and application thereof, so as to realize the comprehensive treatment and application of river silt and steel slag.

[0005] In order to achieve the above objectives, one of the technical solutions adopted by the present invention is: a core-shell solid waste-based functional granular material, comprising a core material and a shell material coated on the surface of the core material; wherein, The nuclear material includes 20-90 parts of river silt, 1-15 parts of hydrogen peroxide, 10-50 parts of rice husk ash, 1-12 parts of sodium hydroxide, and 5-40 parts of desulfurized gypsum; Preferably, the core material includes 24 to 85 parts of river sludge, 4 to 9 parts of hydrogen peroxide, 13 to 43 parts of rice husk ash, 2 to 9 parts of sodium hydroxide, and 10 to 35 parts of desulfurized gypsum.

[0006] The shell material includes 10-100 parts of steel slag, 5-40 parts of slag, 5-30 parts of desulfurized gypsum, and 2-13 parts of polyvinyl alcohol; Preferably, the shell material includes 27 to 90 parts of steel slag, 9 to 32 parts of slag, 8 to 27 parts of desulfurized gypsum, and 3 to 10 parts of polyvinyl alcohol.

[0007] The hydrogen peroxide in the core material can help the river silt decompose into carbon dioxide, which can not only optimize the internal pore structure of the pellets, but also benefit the internal mineralization of the pellets, thereby improving the mechanical properties of the pellets; and the generated carbon dioxide escapes to the shell layer and forms calcium carbonate with free calcium oxide, further improving the mechanical properties of the pellets; the heat released in the above process helps to increase the degree of hydrothermal reaction in the core layer micro-area, thereby improving the overall reaction efficiency.

[0008] The organic matter in the river silt can undergo an esterification reaction with the polyvinyl alcohol in the shell material under the action of sodium hydroxide to form a cross-linked structure at the core-shell interface, further enhancing the bonding strength of the core-shell interface, thereby improving the overall strength of the functional granules.

[0009] In addition, rice husk ash can react with sodium hydroxide to generate sodium silicate to synergistically optimize the bonding strength of the core-shell interface and enhance the overall strength of the functional pellets.

[0010] Furthermore, the particle size of the steel slag is 0.1~3 mm.

[0011] Further, the weight ratio of river silt to hydrogen peroxide is 3 to 15:1; Preferably, the weight ratio of river sludge to hydrogen peroxide is 6 to 10:1. Further, the concentration of hydrogen peroxide is not less than 8%; Preferably, the concentration of hydrogen peroxide is 8 to 20%.

[0012] By controlling the concentration of hydrogen peroxide, the excessive self-decomposition of hydrogen peroxide is suppressed to ensure that hydrogen peroxide fully catalyzes humus. When the concentration of hydrogen peroxide is not less than 8%, the catalytic reaction of hydrogen peroxide on river silt can dominate the reaction; when the concentration of hydrogen peroxide is lower than 8%, the degree of hydrogen peroxide catalyzing river silt to produce carbon dioxide decreases.

[0013] Further, the weight ratio of sodium hydroxide to rice husk ash is 1:3~6.

[0014] Further, the weight ratio of core material to shell material is 1.5~2.5:1; Preferably, the weight ratio of the core material to the shell material is 1.8-2.2:1.

[0015] The second technical solution adopted by the present invention is: a method for preparing the above-mentioned core-shell solid waste-based functional granules, comprising the following steps: (1) placing the core material in an extruder for extrusion molding, and cutting it into small core material segments of 10 to 30 mm; (2) After placing the small pieces of core material in a disc ball making machine for shaping for a period of time, the shell material is added and further shaped to form a spherical green body; (3) placing the spherical green body into a curing kiln and reacting it at 60-80°C for 0.5-1.5h to obtain pre-cured pellets; (4) The pre-cured pellets are placed in a hydrothermal reactor and reacted at 160-180°C for 2-8 hours. After the reaction is completed, the temperature is lowered to obtain functional pellets.

[0016] In step (2), an appropriate amount of water is sprayed during the shaping process, specifically 10-20% of the shell material mass, to facilitate better shaping.

[0017] The third technical solution adopted by the present invention is: an application of any of the above-mentioned core-shell solid waste-based functional granules in water treatment.

[0018] During the water treatment process, the river silt components in the core material can form complexes with organic matter in the polluted water, which is beneficial to the functionality of the pellets; the steel slag in the shell material can treat zinc (Zn), chromium (Cr), copper (Cu) and other ions in the water through chemical precipitation and adsorption, and its good structural strength is also beneficial to improving the overall anti-scouring effect of the functional pellets, so as to improve the service performance and life of the pellets; polyvinyl alcohol has good hydrophilicity, which can reduce the surface tension of water, and can make the functional pellets easier to contact with water, so as to better play the water treatment effect.

[0019] The use of 0.1~3mm steel slag particles can ensure that the shell has good strength and form relatively loose interconnecting holes. In this way, when the functional particles are used for water treatment, water can enter the interior of the functional particles through the interconnecting holes to improve the biofilm formation efficiency and better treat harmful substances and heavy metals in the water through chemical precipitation and adsorption to improve the water treatment effect.

[0020] The beneficial effects of the method for preparing core-shell solid waste-based functional granules of the present invention are: (1) The present invention uses river silt, hydrogen peroxide, rice husk ash, sodium hydroxide, and desulfurized gypsum as core materials, and steel slag, slag, desulfurized gypsum, and polyvinyl alcohol as core materials to prepare core-shell solid waste-based functional granules with good performance.

[0021] (2) The sludge and hydrogen peroxide in the core material can fully react and decompose to produce carbon dioxide, which, on the one hand, helps to optimize the internal porosity of the functional aggregates and is beneficial to the internal mineralization of the aggregates, thereby optimizing the mechanical strength of the aggregates. On the other hand, carbon dioxide can fully react with the free calcium oxide in the shell layer to produce calcium carbonate, thereby enabling the pre-cured aggregates to have initial strength. The heat released by the reaction helps to increase the degree of hydrothermal reaction in the core layer micro-region, further improving the mechanical strength of the aggregates.

[0022] (3) Rice husk ash and sodium hydroxide can generate sodium silicate to enhance the core-shell interface bonding strength, thereby improving the performance of the pellets.

[0023] (4) During the hydrothermal reaction, the organic matter in the river silt decomposes to produce small molecular carboxylic acids, which react with sodium hydroxide to form sodium carboxylate, and then undergo esterification reaction with polyvinyl alcohol under alkaline heating conditions to form a cross-linked structure between the polyvinyl alcohol molecular chains, thereby making the bond between the core and shell tighter; at the same time, a large amount of CSH gel, tobermorite and other calcium silicate minerals are generated in the core and shell, which is beneficial to the strength of the functional aggregate.

[0024] (5) The preparation method of the present invention can efficiently utilize solid wastes such as river silt and steel slag. Through the core-shell double-layer structure, not only can the reaction between the components of the core material and the shell material be fully utilized, but also the bonding strength between the core material and the shell material can be enhanced through the reaction at the core-shell interface. This ensures that the functional granules prepared have sufficient porosity while greatly improving the structural strength. DETAILED DESCRIPTION

[0025] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more explicit definition of the protection scope of the present invention. It should be noted that the following embodiments are for a better understanding of the present invention, are not limited to the best embodiments, and do not limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0026] It should be noted that, in the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0027] In addition, if the specific experimental steps or conditions are not specified in the examples, the operations or conditions of the conventional experimental steps described in the literature in the art can be carried out. The numerical ranges shown by "~" in the examples indicate the ranges containing the values ​​recorded before and after "~" as the minimum and maximum values, respectively. If the manufacturers of the reagents or instruments are not specified, they are all conventional reagent products that can be obtained commercially.

[0028] The core-shell solid waste-based functional granules of the present invention include a core material and a shell material coated on the surface of the core material, wherein the core material includes 20 to 90 parts of river sludge, 1 to 15 parts of hydrogen peroxide, 10 to 50 parts of rice husk ash, 1 to 12 parts of sodium hydroxide, and 5 to 40 parts of desulfurized gypsum. The shell material includes 10 to 100 parts of steel slag, 5 to 40 parts of slag, 5 to 30 parts of desulfurized gypsum, and 2 to 13 parts of polyvinyl alcohol. In some embodiments, the core material includes 24-85 parts of river sludge, 4-9 parts of hydrogen peroxide, 13-43 parts of rice husk ash, 2-9 parts of sodium hydroxide, and 10-35 parts of desulfurized gypsum. The shell material includes 27-90 parts of steel slag, 9-32 parts of slag, 8-27 parts of desulfurized gypsum, and 3-10 parts of polyvinyl alcohol.

[0029] In some embodiments, during the preparation process, the weight ratio of the core material to the shell material placed in the disc pelletizer is 1.5~2.5:1.

[0030] In some embodiments, during the preparation process, the weight ratio of the core material to the shell material placed in the disc pelletizer is 1.8~2.2:1.

[0031] In some embodiments, the weight ratio of river sludge to hydrogen peroxide is 3 to 15:1.

[0032] In some embodiments, the weight ratio of river sludge to hydrogen peroxide is 6 to 10:1. When the concentration of hydrogen peroxide is high, the reaction of hydrogen peroxide catalyzing the release of carbon dioxide from river silt is the dominant reaction. When the concentration of hydrogen peroxide is low, the degree of hydrogen peroxide catalyzing the release of carbon dioxide from river silt is reduced. Based on this, in some embodiments, the concentration of hydrogen peroxide is not less than 8%.

[0033] In some embodiments, the concentration of hydrogen peroxide is 8-20%.

[0034] In some embodiments, the weight ratio of sodium hydroxide to hydrogen peroxide is 1:3-6.

[0035] In some embodiments, the particle size of the steel slag is 0.1-3 mm. In this way, the larger particle size of the steel slag is used to form loose interconnecting holes on the shell to increase the porosity of the shell part, while ensuring that the shell has good strength. When the functional granules are used for water treatment, it is easy for water to enter the interior of the functional granules to improve the biofilm formation efficiency, so as to better treat zinc, chromium, copper and other ions in the water through chemical precipitation and adsorption to optimize the water treatment effect.

[0036] The present invention also provides a method for preparing core-shell solid waste-based functional granules, comprising the following steps: (1) placing the core material in an extruder for extrusion molding, and cutting it into small core material segments of 10 to 30 mm; (2) Put the small pieces of core material into a disc ball making machine and shape them for 1 to 3 minutes, then add the shell material and continue shaping to form a spherical green body; (3) placing the spherical green body into a curing kiln and reacting it at 60-80°C for 0.5-1.5h to obtain pre-cured pellets; (4) The pre-cured pellets are placed in a hydrothermal reactor and reacted at 160-180°C for 2-8 hours. After the reaction is completed, the temperature is lowered to obtain functional pellets.

[0037] In step (2), a proper amount of water is sprayed during shaping, specifically 10-20% of the mass of the shell material, to facilitate better shaping.

[0038] Through the arrangement of steps (1) and (2), the shell material can be coated on the surface of the core material, so that the spherical green body forms a core-shell double-layer structure; through the pre-curing treatment of step (3), the river silt and hydrogen peroxide in the core material can fully react and decompose to generate carbon dioxide, which not only improves the mineralization degree and porosity of the core structure, but also reacts with the free calcium oxide in the shell structure to generate calcium carbonate, thereby improving the density and structural strength of the pre-cured particle size; at the same time, the rice husk ash and sodium hydroxide can react in the first stage at low temperature to generate a small amount of sodium silicate to further increase the mineralization degree and porosity of the core structure. Strengthen the overall strength; through step (4), hydrothermal reaction and esterification reaction occur simultaneously, so that a large amount of CSH gel and tobermorite and other calcium silicate minerals are simultaneously generated in the core and shell; wherein, rice husk ash further reacts with sodium hydroxide to generate sodium silicate, organic matter in river sludge decomposes to generate small molecular carboxylic acid, carboxylic acid reacts with sodium hydroxide to generate sodium carboxylate, and then esterification reaction occurs with polyvinyl alcohol under alkaline heating conditions to form a cross-linked structure between the polyvinyl alcohol molecular chains, thereby making the bonding between the core and the shell tighter, thereby improving the strength of the functional granules.

[0039] When the functional granules prepared by the present invention are applied to water treatment fields such as biological filters, landscape water bodies, wetland substrates, and sewage treatment, the high porosity of the functional granules can fully adsorb harmful substances and heavy metals in the water, thereby improving the water treatment effect.

[0040] Example 1 The following preparation method is used to prepare the functional granules, and the specific steps are as follows: (1) 47 parts of river silt, 6 parts of 15% hydrogen peroxide, 24.5 parts of rice husk ash, 5 parts of sodium hydroxide, and 19.7 parts of desulfurized gypsum were uniformly mixed and placed in an extruder for extrusion molding, and then cut into 20 mm core material segments; (2) uniformly mixing 54 parts of steel slag, 19 parts of slag, 16 parts of desulfurized gypsum, and 6 parts of polyvinyl alcohol to obtain a shell material; placing a small segment of the core material in a disc pelletizer for shaping for 2 minutes, adding the shell material and the small segment of the core material to roll and collide with each other, so that the weight ratio of all the small segments of the core material to the shell material in the disc pelletizer is 2:1, and spraying an appropriate amount of water (15% of the mass of the shell material) during the shaping process to form a spherical green body; (3) placing the spherical green body into a curing kiln and reacting at 70°C for 1 hour to obtain pre-cured pellets; (4) The pre-cured pellets are placed in a hydrothermal reactor and reacted at 170°C for 6 hours. After the reaction is completed, the temperature is lowered to obtain functional pellets.

[0041] Example 2 The following preparation method is used to prepare the functional granules, and the specific steps are as follows: (1) 24 parts of river silt, 4 parts of 8% hydrogen peroxide, 13 parts of rice husk ash, 2.6 parts of sodium hydroxide, and 10.4 parts of desulfurized gypsum were uniformly mixed and placed in an extruder for extrusion molding, and then cut into 20 mm core material segments; (2) uniformly mixing 27 parts of steel slag, 9.5 parts of slag, 8 parts of desulfurized gypsum, and 3 parts of polyvinyl alcohol to obtain a shell material; placing a small segment of the core material in a disc pelletizer and shaping it for 1 minute, adding the shell material and the small segment of the core material to roll and collide with each other, so that the weight ratio of all the small segments of the core material to the shell material in the disc pelletizer is 2:1, and spraying an appropriate amount of water (15% of the mass of the shell material) during the shaping process to form a spherical green body; (3) placing the spherical green body into a curing kiln and reacting at 60°C for 1.5 hours to obtain pre-cured pellets; (4) The pre-cured pellets are placed in a hydrothermal reactor and reacted at 160°C for 7 hours. After the reaction is completed, the temperature is lowered to obtain functional pellets. Example 3 The following preparation method is used to prepare the functional granules, and the specific steps are as follows: (1) 85 parts of river silt, 8.5 parts of 20% hydrogen peroxide, 43 parts of rice husk ash, 8.7 parts of sodium hydroxide, and 34.5 parts of desulfurized gypsum were uniformly mixed and placed in an extruder for extrusion molding, and then cut into 20 mm core material segments; (2) uniformly mixing 90 parts of steel slag, 32 parts of slag, 27 parts of desulfurized gypsum and 10 parts of polyvinyl alcohol to obtain a shell material; placing a small segment of the core material in a disc pelletizing machine for shaping for 3 minutes, adding the shell material and the small segment of the core material to roll and collide with each other, so that the weight ratio of all the small segments of the core material to the shell material in the disc pelletizing machine is 2:1, and spraying an appropriate amount of water (15% of the mass of the shell material) during the shaping process to form a spherical green body; (3) placing the spherical green body into a curing kiln and reacting it at 80°C for 0.5h to obtain pre-cured pellets; (4) The pre-cured pellets are placed in a hydrothermal reactor and reacted at 180°C for 5 hours. After the reaction is completed, the temperature is lowered to obtain functional pellets.

[0042] Example 4 The difference between this embodiment and embodiment 1 is that the core material components in step (1) include 49.5 parts of river sludge, 3.5 parts of 15% hydrogen peroxide, 24.5 parts of rice husk ash, 5 parts of sodium hydroxide, and 19.7 parts of desulfurized gypsum. According to calculation, the mass ratio of river sludge to hydrogen peroxide is 14.1:1.

[0043] Example 5 The difference between this embodiment and embodiment 1 is that the core material components in step (1) include 40 parts of river sludge, 13 parts of 15% hydrogen peroxide, 24.5 parts of rice husk ash, 5 parts of sodium hydroxide, and 19.7 parts of desulfurized gypsum. According to calculation, the mass ratio of river sludge to hydrogen peroxide is 3.1:1.

[0044] Comparative Example 1 The difference between this comparative example and Example 1 is that no hydrogen peroxide is added in step (1).

[0045] Comparative Example 2 The difference between this comparative example and Example 1 is that no sodium hydroxide is added in step (1).

[0046] Comparative Example 3 The difference between this comparative example and Example 1 is that no polyvinyl alcohol is added to the shell material in step (2).

[0047] Comparative Example 4 The difference between this comparative example and Example 1 is that the concentration of hydrogen peroxide in step (1) is 5%.

[0048] Comparative Example 5 The difference between this comparative example and Example 1 is that the pre-curing temperature in step (3) is 100°C.

[0049] Experimental example The functional granules prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to performance tests. The test methods were as per CJ / T229-2008 “Artificial ceramsite filter material for water treatment”. The test results are shown in Table 1.

[0050] Table 1 Test results of Examples 1-5 and Comparative Examples 1-5

[0051] From Table 1, we can see: According to the test results of Examples 1-3, the bulk density of the obtained functional granules is ≤0.95 g / cm 3 , cylinder pressure strength ≥14.51MPa, porosity ≥62%, and the performance is relatively excellent. The reason is that: while using the preparation method of the present invention, the weight ratio of river sludge to hydrogen peroxide in Examples 1-3 is controlled between 6 and 10:1, the weight ratio of hydrogen peroxide to rice husk ash is controlled between 1:3 and 6, and the concentration of hydrogen peroxide is controlled between 8 and 20%, so that hydrogen peroxide can fully catalyze the sludge to generate carbon dioxide, while enhancing the internal mineralization degree and porosity, carbon dioxide can react with calcium oxide to generate calcium carbonate, further improving the density and strength of the pellets; hydrogen peroxide itself can also decompose to produce oxygen to further improve the porosity; and rice husk ash can fully react with sodium hydroxide to generate sodium silicate to improve the core-shell interface adhesion, and the esterification reaction between sludge and polyvinyl alcohol can also further improve the core-shell interface adhesion, which is beneficial to the strength improvement of the functional pellets. The above shows that the functional pellets prepared by the present invention can obtain relatively excellent performance.

[0052] Compared with Example 1, the amount of hydrogen peroxide used in Example 4 is significantly reduced (the weight ratio of river sludge to hydrogen peroxide is 14.1:1), the catalytic effect on the river sludge is significantly weakened, and the amount of carbon dioxide generated is significantly reduced, which not only weakens the optimization effect of the internal pore structure of the pellets and the internal mineralization effect, but also affects the mechanical properties of the pellets; and there is not enough carbon dioxide to escape into the shell material to react with the steel slag to generate calcium carbonate that is beneficial to strength, so the strength and porosity of the functional pellets in Example 4 are both reduced.

[0053] Compared with Example 1, the amount of hydrogen peroxide used in Example 5 is significantly increased (the weight ratio of river sludge to hydrogen peroxide is 3.1:1), the catalytic effect on river sludge is significantly enhanced, the rate of generating carbon dioxide is faster, and the internal pore structure of the functional granules may be damaged. Therefore, although the porosity of the functional granules is increased, the cylinder pressure strength is also greatly reduced.

[0054] Compared with Example 1, no hydrogen peroxide is added in Comparative Example 1, and therefore, it cannot help the river silt to produce carbon dioxide, and can neither optimize the internal pore structure of the functional granules, nor achieve internal mineralization of the functional granules, affecting the mechanical properties of the functional granules; in addition, no carbon dioxide is generated inside the functional granules, and it cannot generate calcium carbonate with the free calcium in the shell material to optimize the density and mechanical properties of the functional granules. Therefore, the packing density of the functional granules increases, while the porosity and cylinder pressure strength decrease.

[0055] Compared with Example 1, no sodium hydroxide was added in Comparative Example 2. On the one hand, the alkalinity in the reaction system was reduced and the degree of reaction was reduced. On the other hand, the lack of sodium hydroxide could not generate sodium silicate with rice husk ash, resulting in a decrease in the degree of core-shell interface bonding. Therefore, the cylinder compressive strength of the functional granules was significantly reduced.

[0056] Compared with Example 1, no polyvinyl alcohol was added in Comparative Example 3. During the hydrothermal reaction of the functional granules, it was unable to undergo esterification reaction with organic matter in the river silt and could not further improve the bonding degree of the core-shell interface. Therefore, the cylinder compressive strength of the functional granules decreased.

[0057] Compared with Example 1, the concentration of hydrogen peroxide in Comparative Example 4 is too low, the catalytic effect on the sludge is weakened, the carbon dioxide generated is reduced, the degree of optimization of the internal pore structure of the pellets is reduced, and the internal mineralization degree is significantly reduced, and the calcium carbonate generated by the reaction with the shell material is reduced. Therefore, the cylinder compressive strength and porosity of the functional pellets are reduced.

[0058] Compared with Example 1, Comparative Example 5 increases the pre-curing temperature to 100°C, and hydrogen peroxide undergoes a more violent self-decomposition phenomenon in the pre-curing stage, resulting in a weakened catalytic effect of hydrogen peroxide on river silt. Although the oxygen produced by the self-decomposition of hydrogen peroxide is beneficial to the improvement of porosity, it is not beneficial to the internal mineralization of the functional pellets, nor can it cooperate with the shell material to generate calcium carbonate, which affects the density of the functional pellets. Therefore, the cylinder compressive strength of the functional pellets is significantly reduced.

[0059] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A core-shell solid waste-based functional granular material, characterized in that: It comprises a core material and a shell material coated on the surface of the core material; wherein, The core material includes 20 to 90 parts of river sludge, 1 to 15 parts of hydrogen peroxide, 10 to 50 parts of rice husk ash, 1 to 12 parts of sodium hydroxide, and 5 to 40 parts of desulfurized gypsum; The shell material includes 10 to 100 parts of steel slag, 5 to 40 parts of slag, 5 to 30 parts of desulfurized gypsum, and 2 to 13 parts of polyvinyl alcohol.

2. The core-shell solid waste-based functional granular material according to claim 1, characterized in that: The weight ratio of the river sludge to hydrogen peroxide is 3-15:

1.

3. The core-shell solid waste-based functional granular material according to claim 1, characterized in that: The weight ratio of the river sludge to hydrogen peroxide is 6-10:

1.

4. The core-shell solid waste-based functional granular material according to claim 1, characterized in that: The concentration of the hydrogen peroxide is not less than 8%.

5. The core-shell solid waste-based functional granular material according to claim 1, characterized in that: The concentration of the hydrogen peroxide is 8% to 20%, and the weight ratio of the sodium hydroxide to the rice husk ash is 1:3 to 6.

6. The core-shell solid waste-based functional granular material according to claim 1, characterized in that: The core material includes 24 to 85 parts of river sludge, 4 to 9 parts of hydrogen peroxide, 13 to 43 parts of rice husk ash, 2 to 9 parts of sodium hydroxide, and 10 to 35 parts of desulfurized gypsum.

7. The core-shell solid waste-based functional granular material according to claim 1, characterized in that: The shell material includes 27 to 90 parts of steel slag, 9 to 32 parts of slag, 8 to 27 parts of desulfurized gypsum, and 3 to 10 parts of polyvinyl alcohol.

8. The core-shell solid waste-based functional granular material according to claim 1, characterized in that: The particle size of the steel slag is 0.1-3 mm.

9. A method for preparing the core-shell solid waste-based functional granules according to any one of claims 1 to 8, characterized in that: The steps include: The core material is placed in an extruder for extrusion molding, and then cut into small core material segments of 10 to 30 mm; After a small section of the core material is placed in a disc ball making machine and shaped for a period of time, the shell material is added and further shaped to form a spherical green body; The spherical green body is placed in a curing kiln and reacted at 60-80°C for 0.5-1.5h to obtain pre-cured pellets; The pre-cured pellets are placed in a hydrothermal reactor and reacted at 160-180°C for 2-8 hours. After the reaction is completed, the temperature is lowered to obtain functional pellets.

10. Use of the core-shell solid waste-based functional granules according to any one of claims 1 to 8 in water treatment.

Citation Information

Patent Citations

  • River-lake sludge-based unfired ultralight ceramsite, preparation method and application thereof

    CN110862252A

  • Core-shell lightweight aggregate containing high-content sludge and preparation method of core-shell lightweight aggregate

    CN113121139A

  • Sintering-free ceramsite and preparation method thereof

    CN114920530A

  • Preparation method of solid waste solidified river sediment heavy metal and unfired shell-wrapped ceramsite and river sediment-based unfired shell-wrapped ceramsite

    CN116375378A

  • High-strength and high-toughness steel slag-based cementing material and preparation method thereof

    CN117550867A

Cited By

  • Preparation method of biomass aggregate lightweight wall impervious concrete and concrete

    CN121377683A